Cross‐scale controls on carbon emissions from boreal forest megafires. (16th May 2018) - Walker, Xanthe J.; Rogers, Brendan M.; Baltzer, Jennifer L.; Cumming, Steven G.; Day, Nicola J.; Goetz, Scott J.; Johnstone, Jill F.; Schuur, Edward A. G.; Turetsky, Merritt R.; Mack, Michelle C.
Abstract: Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories (NWT), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer (SOL) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale. Abstract : We assessed both aboveground and soil organic layer combustion, with the goal of determining the major drivers in total carbon (C) combustion after an unprecedentedly large area burned in 2014 in the Taiga Shield and Taiga Plains ecozones of the Northwest Territories, Canada. On average, 3.35 kg C m −2 was combusted. Total C emissions were (i) greatest in forest stands located at landscape positions with intermediate drainage, (ii) increased with the proportion of black spruce stems relative to all stems in the plot, and were not impacted by variables associated with fire weather or date of burn.